Acute cerebrovascular disease in the young: the Stroke in Young Fabry Patients Study - Rolfs, Arndt; Lichy, Christoph; Hennerici, Michael G.; Fazekas, Franz; Grittner, Ulrike; Dichgans, Martin; Martus, Peter; Holzhausen, Martin; Böttcher, Tobias; Heuschmann, Peter U.; Tatlisumak, Turgut; Tanislav, Christian; et al. (Stroke, 2013)
Background and Purpose — Strokes have especially devastating implications if they occur early in life; however, only limited information exists on the characteristics of acute cerebrovascular disease in young adults. Although risk factors and manifestation of atherosclerosis are commonly associated with stroke in the elderly, recent data suggests different causes for stroke in the young. We initiated the prospective, multinational European study Stroke in Young Fabry Patients (sifap) to characterize a cohort of young stroke patients. Methods — Overall, 5023 patients aged 18 to 55 years with the diagnosis of ischemic stroke (3396), hemorrhagic stroke (271), transient ischemic attack (1071) were enrolled in 15 European countries and 47 centers between April 2007 and January 2010 undergoing a detailed, standardized, clinical, laboratory, and radiological protocol. Results — Median age in the overall cohort was 46 years. Definite Fabry disease was diagnosed in 0.5% (95% confidence interval, 0.4%-0.8%; n=27) of all patients; and probable Fabry disease in additional 18 patients. Males dominated the study population (2962/59%) whereas females outnumbered men (65.3%) among the youngest patients (18-24 years). About 80.5% of the patients had a first stroke. Silent infarcts on magnetic resonance imaging were seen in 20% of patients with a first-ever stroke, and in 11.4% of patients with transient ischemic attack and no history of a previous cerebrovascular event. The most common causes of ischemic stroke were large artery atherosclerosis (18.6%) and dissection (9.9%). Conclusions — Definite Fabry disease occurs in 0.5% and probable Fabry disease in further 0.4% of young stroke patients. Silent infarcts, white matter intensities, and classical risk factors were highly prevalent, emphasizing the need for new early preventive strategies. Clinical Trial Registration Information — URL: http://www.clinicaltrials.gov.Unique identifier: NCT00414583